Methodologies for systematic reviews with meta-analysis of randomised clinical trials in pain, anaesthesia, and perioperative medicine. (April 2021) - Doleman, Brett; Mathiesen, Ole; Jakobsen, Janus C.; Sutton, Alex J.; Freeman, Suzanne; Lund, Jonathan N.; Williams, John P.
Summary: Systematic reviews and meta-analyses (SRMAs) are increasing in popularity, but should they be used to inform clinical decision-making in anaesthesia? We present evidence that the certainty of evidence from SRMAs in anaesthesia (and in general) may be unacceptably low because of risks of bias exaggerating treatment effects, unexplained heterogeneity reducing certainty in estimates, random errors, and widespread prevalence of publication bias. We also present the latest methodological advances to help improve the certainty of evidence from SRMAs. The target audience includes both review authors and practising clinicians to help with SRMA appraisal. Issues discussed include minimising risks of bias from included trials, trial sequential analysis to reduce random error, updated methods for presenting effect estimates, and novel publication bias tests for commonly used outcome measures. These methods can help to reduce spurious conclusions on clinical significance, explain statistical heterogeneity, and reduce false positives when evaluating small-study effects. By reducing concerns in these domains of Grading of Recommendations, Assessment, Development and Evaluation, it should help improve the certainty of evidence from SRMAs used for decision-making in anaesthesia, pain, and perioperative medicine.